Effects of Crude Oil Prices Volatility, the Internet and Inflation on Economic Growth in ASEAN-5 Countries: A Panel Autoregressive Distributed Lag Approach - Rosnawintang, Rosnawintang; Tajuddin, Tajuddin; Adam, Pasrun; Pasrun, Yuwanda Purnamasari; Saidi, La Ode (International Journal of Energy Economics and Policy, 2020)
This paper aims to examine the effect of crude oil price volatility, the internet, and inflation on economic growth in ASEAN-5 countries (Indonesia, Malaysia, the Philippines, Singapore, and Thailand). To test this effect, we use the panel Autoregressive Distributed Lag model and panel data with annual time series for the period from 1995 to 2018. The test results show that only the internet affects economic growth in the long run, and this effect is positive. Meanwhile, in the short run, there is an impact of crude oil price volatility, the internet, and inflation on economic growth in all ASEAN-5 countries. However, the effect of inflation on economic growth only exists in Indonesia, the Philippines, Singapore, and Thailand. Keywords: Crude oil price volatility, the internet, inflation, economic growth, Autoregressive Distributed Lag Model, Pooled Mean Group. JEL Classifications: C330, E310, E230, O330 DOI: https://doi.org/10.32479/ijeep.10395